APLIKASI FOODCOURTMENGGUNAKAN MICROSOFT VISUAL STUDIO2008 - Hardiyanti, Tri (Prosiding KOMMIT, 2012)
Advances in computer technology requires computerization in all fields including ordering food and beverages at a food court,theauthors want to try by means of computerizedso that the application is expectedto assist in theprocessof serving food and drinks menu a restaurant which is located ina food court, and assist the process and generate a good dealof information quickly and accurately. Results obtained inscientific writing is to obtain the information presented in the form of food and beverage menu along with a description of the price of each menu. This foodcourt applications created using Microsoft VisualStudio2008 where applications can provide convenience to the user inthis case is the consumer.